2021
DOI: 10.1073/pnas.2106744118
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectral weight, phase stiffness, and T c bounds for trivial and topological flat band superconductors

Abstract: We present exact results that give insight into how interactions lead to transport and superconductivity in a flat band where the electrons have no kinetic energy. We obtain bounds for the optical spectral weight for flat-band superconductors that lead to upper bounds for the superfluid stiffness and the two-dimensional (2D) Tc. We focus on on-site attraction |U| on the Lieb lattice with trivial flat bands and on the π-flux model with topological flat bands. For trivial flat bands, the low-energy optical spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The relationship between the superfluid weight and quantum metric has been used to derive various bounds for the superfluid weight [5,6,13,23,54]. The lower bound given in [5] for time-reversal-symmetric systems in terms of the spin Chern number is valid, as it is a lower bound for the quantum metric regardless of the choice of orbital positions.…”
Section: Revisiting the Literaturementioning
confidence: 99%
“…The relationship between the superfluid weight and quantum metric has been used to derive various bounds for the superfluid weight [5,6,13,23,54]. The lower bound given in [5] for time-reversal-symmetric systems in terms of the spin Chern number is valid, as it is a lower bound for the quantum metric regardless of the choice of orbital positions.…”
Section: Revisiting the Literaturementioning
confidence: 99%
“…Our results are not related to topological effects [62,63], since the bandstructure of the bilayer system is nontopological and the wide band features no gap. The findings are also qualitatively different from the previous results related to incipient bands [26][27][28][29][30][31][32], since these works considered the effects of full or empty narrow bands in repulsive models and found that the half-filled situation does not favor superconductivity [29].…”
mentioning
confidence: 52%
“…The physics of two-body bound states in the presence of a flat band has been recently explored theoretically in different contexts, including topological matter [17][18][19][20] and the link between the inverse effective mass of the bound state and the quantum metric of the singleparticle states [21][22][23]. This second direction is related to the more general question of understanding how transport and superconductivity can occur in system with quenched kinetic energy [24][25][26][27][28][29][30][31][32]. Transport in many-body bosonic flat-band systems has also been explored, see for instance [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%